The Philosophical Foundations of Islamic Educational Management: An Epistemological Analysis of Modern Management Theory - Imam Buchori; Iriyanto Iriyanto; Herri Azhari; Romi Sumarlin; Agus Sujarwo (al-Afkar, Journal For Islamic Studies, 2026)
This study examines the philosophical foundations of Islamic Educational Management (IEM) through an epistemological analysis of modern management theory. The rapid adoption of modern management models in educational institutions has raised critical questions regarding their philosophical compatibility with Islamic values and educational objectives. Using a qualitative, library-based research design and philosophical analysis, this study explores the sources, validity, and assumptions of knowledge underlying both Islamic educational management and modern management theory. The findings reveal that IEM is grounded in a theocentric epistemology that integrates revelation, reason, empirical experience, and ethical consciousness, positioning management as a moral and spiritual responsibility rather than a value-neutral technical process. In contrast, modern management theory is largely rooted in positivist and empiricist epistemologies that emphasize efficiency, productivity, and instrumental rationality. Despite these differences, the study identifies significant points of convergence, particularly in the use of rational planning, organizational systems, and empirical tools. The study argues that modern management knowledge can be selectively integrated into Islamic educational contexts through an epistemological synthesis that aligns efficiency with ethical and spiritual accountability. This research contributes to the theoretical development of Islamic educational management by offering a conceptual framework that bridges modern management theory and Islamic epistemology, and provides philosophical guidance for educational leaders seeking value-based and contextually relevant management practices.